MINCER micrometerological station used to improve spikelet sterility estimations in crop models for rice - CGIAR Research Program on Rice (2021)
The MINCER is readily available for use and a network was established based on MINCER, called MINCERnet, for monitoring the thermal environment within the rice canopy in paddy fields and for collecting other crop data. Preprinted paper is available, and paper is under review.